Trimethoxycinnamates and Their Cholinesterase Inhibitory Activity - Kos, Jiri; Strharsky, Tomas; Štěpánková, Šárka; Svrčková, Katarína; Oravec, Michal; Hosek, Jan; Imramovský, Aleš; Jampilek, Josef (MDPI, 2021)
A series of twelve nature-inspired 3,4,5-trimethoxycinnamates were prepared and characterized. All compounds, including the starting 3,4,5-trimethoxycinnamic acid, were tested for their ability to inhibit acetylcholinesterase (AChE) and butyrylcholinesterase (BChE) in vitro; the selectivity index (SI) was also determined. 2-Fluororophenyl (2E)-3-(3,4,5-trimethoxyphenyl)-prop-2-enoate demonstrated the highest SI (1.71) in favor of BChE inhibition. 2-Chlorophenyl (2E)-3-(3,4,5-trimethoxyphenyl)prop-2-enoate showed the highest AChE-inhibiting (IC50 = 46.18 mu M) as well as BChE-inhibiting (IC50 = 32.46 mu M) activity with an SI of 1.42. The mechanism of action of the most potent compound was determined by the Lineweaver-Burk plot as a mixed type of inhibition. An in vitro cell viability assay confirmed the insignificant cytotoxicity of the discussed compounds on the two cell lines. Trends between structure, physicochemical properties and activity were discussed.
Trimethoxycinnamáty a jejich cholinesterázová inhibitorní aktivita
Keywords: trimethoxycinnamates; cholinesterase-inhibiting activity; cytotoxicity; trimethoxycinamáty; inhibiční aktivita cholinesterázy; cytotoxicita